China's Impacts on SSA through the Lens of Growth and Exports - Mu, Yibin (IMF Working Papers; Working Paper ;, 2017)
The analysis of China's impacts on the 44 SSA countries reveals that: (i) after joining the WTO in 2001, China has started to impact significantly on SSA growth: one-percent increase in China's GDP per capita leads to 0.02 percent increase on the SSA's GDP per capita; (ii) oil and investment-goods exporters benefit more from China's growth; (iii) compared to China's consumption, its investment growth acts as a more important channel in influencing SSA; (iv) exports to China, highly linked to China's growth, is an important indicator for SSA's exports. Our results call for SSA countries to be well prepared for China's rebalancing given its growing economic influence and to proactively search a sustainable way to continuously enhance productivity.